Literary Appreciation Forms by PBSI College Students of University Muhammadiyah Tangerang in the Short Stories Collection of Kompas Newspaper - Dwi Hudhana, Winda (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The purpose of this study is to describe the form of students’ literary appreciation for the collection of short stories in the Kompas Newspaper. A qualitative approach with descriptive methods was used in this study. The objec of this research is a short story from the Kompas Newspaper. This study subjects were PBSI UMT 7th semester students. The results of the study are 1) interest in short stories, 8.6% of students like but are not interested in reading short stories and 13.4% of students do not like and are not interested in reading short stories. 2) the analysis process, 78% of students are able to determine the right approach in short story appreciation, 12% of students are unable to determine the right approach in short story appreciation. 3) Understanding of literary works, 52% of students find it difficult to understand short stories and as many as 48% of students easily understand the contents of short stories. 4) implementation of the literary approach, 48% of students had no difficulty understanding the approach and 52% of students had difficulty. 5) Difficulty of analysis, 69.5% of students have difficulty in analyzing short stories and 30.5% of students have no difficulty in analyzing short stories. 6) search for literary references, there are 65% of students have difficulty finding references and 35% of students are able to find references.